Improvement of PVC Doll Production Line Efficiency through Integration of Time Study and Ranked Positional Weight Method in Line Balancing - Sita Kurniaty; Ade Irpan Sabilah (LPPMP Universitas Bhayangkara Jakarta Raya, 2026)
This study aims to improve the efficiency of the PVC doll production line at CV. Eye Wind by integrating Time Study and Line Balancing methods using the Ranked Positional Weight (RPW). The research began with data uniformity and adequacy tests, followed by determining standard time through Time Study. RPW was applied to balance the production line, while 5 Whys and 5W+1H methods were used to identify root causes and propose improvements. The results show that the stirring process is the main bottleneck with a standard time of 2,941.28 seconds. This study provides accurate work standards and practical recommendations expected to reduce bottlenecks and increase overall production efficiency